# Math differentiation

posted by .

1. y = x^x
2. y = (sin^2xtan^4x)/(x^2+1)^2
3. y = x^(1/x)
4. y = 2^(-x^3)

Okay, so I'm pretty sure 1 is done easily:
ln y = ln (x^x)
ln y = x ln x
d/dx ln y = d/dx x ln x
y'(1/y) = x(1/x) + ln x(1) = 1 + ln x
y'(1/y) = ln x + 1
y' y(1/y) = (ln x + 1)y
y' = (ln x + 1)y

since y = x^x,
y' = (ln x + 1)x^x

For #2, this is as far as I got:
ln y = ln[(sin^2xtan^4x)/(x^2+1)^2
y'(1/y) = ln(sin^2xtan^4x) - ln(x^2+1)^2

What do I do after that?

#3, I thought was like #1, but I still think my answer is incorrect or maybe I didn't simplify properly:
ln y = (1/x) ln x
d/dx ln y = d/dx (1/x) ln x
y'(1/y) = (1/x)*(1/x) + ln x*(-1/x^2) = (1/x)^2 + ln x*(-1/x^2)

y' = (1/x)^2 + ln x*(-1/x^2)y

y' = (1/x)^2 + ln x*(-1/x^2)x^(1/x)

And for #4 I am completely lost since there is an exponent within the exponent. Any kind of hints or clues would be SO appreciated.

• Math differentiation -

#1 is good

in #2 you could go further before taking any derivative
y'(1/y) = ln(sin^2xtan^4x) - ln(x^2+1)^2 or
y'(1/y) = ln(sin^2x) + ln(tan^4x) - 2ln(x^2 + 1)
y'(1/y) = 2ln(sinx) + 4ln(tanx) - 2ln(x^2+1)

and now differentiate it

In #3 from your second last line of
y' = (1/x)^2 + ln x*(-1/x^2)y I would do

y ' = y(1 - lnx)/x^2 and leave it like that

#4 is exponential differentiation.
Notice the base is a constant, not a variable

recall if y = a^u
then y' = (ln a)(a^u)(u')

so for y = 2^(-x^3)
y' = ln2(-3x^2)(2^(-x^3))
= -3ln2(x^2)(2^(-x^3))

If you want to do it by the same method as the above, you would get

lny = ln(2^(-x^3))
= (-x^3)(ln2)
= -ln2(x^3)
now take the derivative

y'/y = -ln2(3)x^2
y' = -3ln2(x^2)y

## Similar Questions

1. ### Algebra II

I'm not quite sure how to set this problem up. This is the first of the entire worksheet and I'm sure if I understand one problem I can finish the rest pretty easily. The problem states: When there is no wind, Amelia flies her plane …
2. ### Calculus

Hi, I'm having trouble using implicit differentiation to determine dy/dx in the form dy/dx = f(x,y) for sin(2x+3y)=3x^3y^2+4 Do I make it sin(2x+3y)-3x^3y^2=4 then differentiate to get 2cos(2x+3y)-9x^2*2y=0 ?
3. ### Public High School Pre Calculus HH

Ok I do not know how to do this problem. I know that csc is simply sin^-1 sin (- pi/12) csc ( (37 pi)/12 ok now I know this also sin (- pi /12 ) = - sin ( pi/12) not really sure how that helps I don't know were to go from here ( - …
4. ### Trigonometry

How do you factor and simplify, 1-sin^3x and sec^4x-2sec^2xtan^2x+tan^4x
5. ### trig

prove: tan*2x-sin*2x=sin*2xtan*2x
6. ### trig

prove: tan*2x-sin*2x=sin*2xtan*2x
7. ### Math-Derivatives.

if y=sec^(3)2x, then dy/dx= my answer is 6 sec^3 2xtan 2x but im not sure if that is right. ?
8. ### Calculus

Find dy/dx for y=sin(x+y) A. 0 B. (cos(x+y))/(1-cos(x+y) C. cos(x+y) D. 1 E. None of these I know I'm supposed to use implicit differentiation but I'm not sure how to go about it with sin
9. ### Math

Let K(x)= (sin(3x-7)) / (e^x-2) (I'm sorry if it is not clear here, but the denominator in K(x) has the natural number, e, to the power of just x. So "x-2" is not the exponent. "x" is the exponent). The Question: Does K(x) have a horizontal …
10. ### Math (Integrals) (Using given method)

I would like to solve the ∫sin^2(pix) dx Using the given substitution identity: sin^2(x) = (1/2)(1-cos2x) This is what I did so far: ∫sin^2(pix) let u = pix du = pi dx (1/pi)∫sin^2(u)du Applying the identity is where I'm lost …

More Similar Questions